Acute antibody‐mediated rejection in ABO‐compatible pediatric liver transplant recipients: case series and review of the literature. (5th September 2016) - Wozniak, Laura J.; Naini, Bita V.; Hickey, Michelle J.; Bhattacharyya, Sarathi; Reed, Elaine F.; Busuttil, Ronald W.; Farmer, Douglas G.; Vargas, Jorge H.; Venick, Robert S.; McDiarmid, Sue V.
Abstract: Acute AMR is well reported following ABO‐incompatible LTx. However, it remains uncommon in ABO‐compatible LTx. It typically presents with graft dysfunction ≤2 weeks post‐LTx and is often associated with graft loss. We report the clinical presentation, treatment regimen, and outcome of six pediatric LTx recipients diagnosed with early acute AMR based on (i) clinical signs of graft dysfunction, (ii) histopathology indicative of acute injury ± C4d staining, and (iii) presence of HLA DSA. All patients developed elevated ALT and GGT ≤ 45 days post‐LTx. All showed HLA class I (n=4) and/or II (n=6) DSA (peak MFI 6153–11 910). Four had de novo DSA, and two had preformed DSA. Five were initially diagnosed with ACR refractory to steroid therapy. Four exhibited resolution of graft dysfunction with AMR therapy. Two had refractory AMR—one was re‐transplanted; the other was treated with eculizumab and showed improvement in graft function but later died due to a tracheostomy complication. Our case series suggests that AMR following ABO‐compatible LTx may be under‐diagnosed. The presentation can be variable, and treatment should be individualized. Eculizumab may be an option for refractory AMR. Ultimately, future multicenter studies are needed to better define diagnostic criteria, characterize optimal treatment, and assess long‐term outcomes following liver AMR.